2014
DOI: 10.1016/j.bmc.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and biological evaluation of ezrin inhibitors targeting metastatic osteosarcoma

Abstract: Respiratory failure due to pulmonary metastasis is the major cause of death for patients with osteosarcoma. However, the molecular basis for metastasis of osteosarcoma is poorly understood. Recently, ezrin, a member of the ERM family of proteins, has been associated with osteosarcoma metastasis to the lungs. The small molecule NSC 668394 was identified to bind to ezrin, inhibit in vitro and in vivo cell migration, invasion, and metastatic colony survival. Reported herein are the design and synthesis of analogu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…However, the effectiveness of this therapy has achieved little improvement in the past 20 years. Recent evidence has shown that pulmonary metastasis is the leading cause of death among osteosarcoma patients, and toxic side effects as well as multidrug resistance to traditional agents were too pronounced to provide any benefit to some patients [9]. Therefore, it is extremely urgent to develop new anti-osteosarcoma drugs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effectiveness of this therapy has achieved little improvement in the past 20 years. Recent evidence has shown that pulmonary metastasis is the leading cause of death among osteosarcoma patients, and toxic side effects as well as multidrug resistance to traditional agents were too pronounced to provide any benefit to some patients [9]. Therefore, it is extremely urgent to develop new anti-osteosarcoma drugs.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, the molecule NSC 668394, identified by Paige at al. [20], binds to ezrin resulting in inhibition of in vitro and in vivo cell migration, invasion, and metastatic colony survival. Wang et al [38] showed AU1751 to be the most effective target site of ezrin mRNA for DNAzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In osteosarcoma, high ezrin expression is linked to pulmonary metastasis and a more aggressive course of disease [18]. There is evidence that suppression of ezrin expression in experimental models results in inhibition of cell growth and reduction of metastatic spread [19,20]. Accordingly, there is a clinical need to validate ezrin expression in patients with osteosarcoma and to assess whether monitoring of changes in levels over the course of treatment predicts treatment response and influences patient survival.…”
Section: Introductionmentioning
confidence: 97%
“…This effect was observed for infected and uninfected HEp-2 cells ( Figures 6C-6E). It has been shown for NSC668394 that it binds to ezrin (Paige et al, 2014). To assess whether disorazoles also bind to ezrin, a binding experiment using surface plasmon resonance (SPR) was performed by using human recombinant ezrin as the ligand and the disorazoles as analytes.…”
Section: Ezrin Is Targeted By Disorazolesmentioning
confidence: 99%